Exploring urban and agricultural land use planning - Zexu Chen; Huachun Dong (Results in Engineering)
Socio-economic development has accelerated urban expansion, leading to the encroachment of urban space into agricultural space land and seriously undermining the stability of ecosystems. Scientifically optimizing the layout of urban-agricultural space can guarantee China's food security, promote urban development and maintain ecological stability. In this study, we focused on the rapidly growing city of Nankang. We used land, ecological and geographic location data to calculate land suitability, predicted future urban space through the GeoSOS-FLUS model, and finally optimized the agricultural-urban space conflict. The results show that: the areas of farmland with quality evaluation results for grades 1–4 were 7783.13 hm2, 9411.01 hm2, 8738.99 hm2 and 3032.73 hm2, and the areas suitable for construction, more suitable for construction, unsuitable for construction and prohibited from construction accounted for 12.19 %, 16.23 %, 41.34 % and 30.24 %, respectively. Combining the FLUS model with the land suitability evaluation results, we found that there is a conflict area of 1841.96 hm2 in the delineation scheme. Adjusting their layout according to the principle of conflict coordination, the optimized area of agricultural-urban space is 28429.34 hm2 and 8968.23 hm2 respectively, accounting for 16.32 % and 5.15 % of the study area. The result of spatial contradiction optimization satisfies the balance between production and residential space, promotes urban development, protects ecological security, and can provide scientific reference for regional urban ecological environment construction.